Evaluasi Keandalan Struktur Atas Gedung Kantor Bupati Ngada di Nagekeo - Laka Suku, Yohanes; Radja, Veronika Miana (TEKNOSIAR, 2024)
Evaluation of the reliability of the upper structure of the Ngada Regent's Office building in Mbay aims to determine the strength of the existing upper structure in accordance with SNI 1726: 2019 concerning Procedures for earthquake resistance planning for building and non-building structures, and SNI 2847: 2019 concerning Requirements for structural concrete for buildings and explanations. From the results of the analysis and evaluation of the cross-sectional strength of structural elements, it was found that there were 16 beams that were unsafe and needed to be strengthened, while the column and plate elements were quite strong and safe.